2017
DOI: 10.17576/gema-2017-1704-05
|View full text |Cite
|
Sign up to set email alerts
|

Metaphor and the Representations of Health and Illness among the Semai Indigenous Community in Malaysia

Abstract: Diverse methods and approaches have been utilised in researching the cultural bases of health, illness and wellbeing. Understanding the cultural representation of health and illness of particular communities becomes urgent especially when the community concerned is underserved in healthcare. In this project, we sought to examine the representations of health and illness by members of the Semai indigenous community through the use of metaphor analysis, a qualitative method in applied linguistics that attend to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In contrast, studies among Orang Asli living in deep forests and inland locations have reported the opposite situation. The Semai from the Senoi group 30 and the Batek from the Negrito group 31 are still primarily practising traditional lifestyles and medicine, especially in the healing of ailments.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies among Orang Asli living in deep forests and inland locations have reported the opposite situation. The Semai from the Senoi group 30 and the Batek from the Negrito group 31 are still primarily practising traditional lifestyles and medicine, especially in the healing of ailments.…”
Section: Discussionmentioning
confidence: 99%
“…Interviews were conducted to elicit narratives from cancer survivors in order to find out their emotional and cognitive states during the process of coping with cancer. The interview guide was based on Acuna et al (2016), Chapman (2001), Lendik et al (2017) and Sairanen (2015). The main questions were as follows: 1.…”
Section: Methodsmentioning
confidence: 99%
“…The common analysis framework of researchers who work within this field is the Conceptual Metaphor Theory (CMT) (Lakoff &Johnson, 1980),which describes the mapping of two domains known as the source and target domains. This theory has been commonly adopted in the analysis of metaphorical expressions in various studies related to certain concepts, such as emotion (Moradi & Mashak, 2014;Türker, 2013), learning (Berendt, 2008;Imran Ho-Abdullah, 2008) and illness (Lendik et al, 2017). The Conceptual Metaphor theory has also been extended to other areas, namely, law (Greenwood, 2005;Hanne & Weisberg, 2018), politics (Charteris-Black, 2011Meisenberg & Meisenberg, 2015), economy (Arrese, 2015;Arrese & Vara-miguel, 2016;Nurul Hijah bte Jasman & Kasim, 2013), psychology (Mc-Mullen & Conway, 2002) and medicine (Ferguson et al, 2010;Golden et al, 2012) due to the pervasive linguistic manifestations of metaphors in different types of discourse.…”
Section: Literature Reviewmentioning
confidence: 99%